Neural heterogeneity underlying late adolescent motivational processing is linked to individual differences in behavioral sensation seeking. Issue 3 (18th January 2022) - Demidenko, Michael I.; Huntley, Edward D.; Weigard, Alexander S.; Keating, Daniel P.; Beltz, Adriene M.
Abstract: Adolescent risk‐taking, including sensation seeking (SS), is often attributed to developmental changes in connectivity among brain regions implicated in cognitive control and reward processing. Despite considerable scientific and popular interest in this neurodevelopmental framework, there are few empirical investigations of adolescent functional connectivity, let alone examinations of its links to SS behavior. The studies that have been done focus on mean‐based approaches and leave unanswered questions about individual differences in neurodevelopment and behavior. The goal of this paper is to take a person‐specific approach to the study of adolescent functional connectivity during a continuous motivational state, and to examine links between connectivity and self‐reported SS behavior in 104 adolescents ( M Age  = 19.3; SD Age  = 1.3). Using Group Iterative Multiple Model Estimation (GIMME), person‐specific connectivity during two neuroimaging runs of a monetary incentive delay task was estimated among 12 a priori brain regions of interest representing reward, cognitive, and salience networks. Two data‐driven subgroups were detected, a finding that was consistent between both neuroimaging runs, but associations with SS were only found in the first run, potentially reflecting neural habituation in the second run. Specifically, the subgroup that had unique connections between reward‐related regions had greater SS and showed a distinctive relation between connectivity strength in the reward regions and SS. These findings provide novel evidence for heterogeneity in adolescent brain‐behavior relations by showing that subsets of adolescents have unique associations between neural motivational processing and SS. Findings have broader implications for future work on reward processing, as they demonstrate that brain‐behavior relations may attenuate across runs. Abstract : Adolescents completed two runs of the monetary incentive delay (MID) task. Using a data‐driven person‐specific network connectivity approach, Group Iterative Multiple Model Estimation (GIMME), we uncovered two subgroups for MID runs. During Run 01, subgroups significantly related to sensation seeking; however, during Run 02 subgroups did not significantly relate to sensation seeking.